An Anthology of the Arts and Crafts Movement - Ashbee, C.R.; Lethaby, W.R.; Gimson, Ernest; Greensted, Mary (Aldershot : Lund Humphries, 2005)
This anthology includes contributions from many of the key practitioners of the Arts and Crafts Movement (including C.R. Ashbee, W.R. Lethaby and Ernest Gimson), as well as from commentators in newspapers and journals. It provides both an introduction to the ideas behind the Arts and Crafts Movement in England in its own words, and a vivid picture of the people and events which shaped the Movement.(bron: achterplat boek)
Adlib record nr. 530010523
Engels
boek
Keywords: Arts and Crafts